System for assessing broilers thermal comfort - Júnior, Arilson José de Oliveira [UNESP] (2021)
One of the ways to optimize animal production environments is through the understanding of the bioclimatic factors that are harmful to the animals. Among the techniques currently applied for measuring and analyzing bioclimatic factors, the vast majority demand that the producers and researchers have high level of technical skills, those techniques (e.g. using maps of spatial variability) hinder the rapid evaluation of certain environments. It is important to note that there is currently no software and hardware tool that allows for an on-site bioclimatic analysis, for example using an Android or iOS app. Thus, the present study was conducted with the objective of developing a system capable of collecting air temperature measurements (Ta), black globe temperature (Tg) and relative humidity (RH), to interact with Aurora mobile app, enabling the on-site development of maps with spatial variability of the air temperature and indices of thermal broilers comfort, using data interpolation. The system was developed through the creation of six transmitters and one receiver. The results obtained indicate that the system operated correctly and allows on-site analysis of thermal animal comfort. During the validation period a total of 48 maps were developed, considering the periods of morning and afternoon, and using the Ta, BGHI and THI measurements. The maps allowed the on-site identification of regions with conditions of comfort, discomfort and thermal stress (both by heat and cold). According to the maps of thermal comfort indices, the afternoon period presented conditions that were often heat stress. The maps of air temperature and thermal comfort indices allow the producers and researchers to have, at hand, a highly portable tool for evaluating the broilers welfare.